How can medical students suffering from hearing loss auscultate their patients? - Riva, Michele Augusto; Bava, Mattia; D'Orso, Marco Italo; De Vito, Giovanni; Cesana, Giancarlo (La Medicina del Lavoro, 2014)
Auscultation is a fundamental part of medical examination.It is generally performed using a stethoscope whichallows listening to body sounds, in particular of the heartand lungs, the function of which can be initially exploredusing this instrument. According to Rabinowitz et al., despiteimprovements in diagnostic technology, “the ability toauscultate a patient’s heart and lungs using a stethoscoperemains the basic occupational skill for physicians”...